1996
DOI: 10.1128/jvi.70.7.4210-4219.1996
|View full text |Cite
|
Sign up to set email alerts
|

A new hepadnavirus endemic in arctic ground squirrels in Alaska

Abstract: We present evidence for a novel member of the hepadnavirus family that is endemic in wild arctic ground squirrels (Spermophylus parryi kennicotti) in Alaska. This virus, designated arctic squirrel hepatitis virus (ASHV), was initially detected in the livers of animals bearing large hepatic nodules by nucleic acid hybridization with hepadnavirus probes and in plasma by cross-reactivity with antibodies to hepadnavirus surface and core antigens. The complete nucleotide sequence of the 3,302-bp-long ASHV genome wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(39 citation statements)
references
References 73 publications
0
38
1
Order By: Relevance
“…Hence, combined with previous studies, these data indicate that bats are an important natural reservoir of orthohepadnaviruses. Although rodents comprise the largest order of mammals (Wilson and Reeder, 2005) and are a major source of zoonotic infectious diseases (Meerburg et al, 2009;Han et al, 2015), to date hepadnaviruses have only been discovered in three species of ground squirrels in the USA (Summers et al, 1978;Marion et al, 1980;Testut et al, 1996). We surveyed 462 rodents from 8 species and 148 Asian house shrews from Zhejiang province.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, combined with previous studies, these data indicate that bats are an important natural reservoir of orthohepadnaviruses. Although rodents comprise the largest order of mammals (Wilson and Reeder, 2005) and are a major source of zoonotic infectious diseases (Meerburg et al, 2009;Han et al, 2015), to date hepadnaviruses have only been discovered in three species of ground squirrels in the USA (Summers et al, 1978;Marion et al, 1980;Testut et al, 1996). We surveyed 462 rodents from 8 species and 148 Asian house shrews from Zhejiang province.…”
Section: Discussionmentioning
confidence: 99%
“…Orthohepadnaviruses infect mammals including humans. Although hepadnaviruses were discovered in ground squirrels (genus Marmota) in the USA (Summers et al, 1978;Marion et al, 1980;Testut et al, 1996), they have been not observed in other rodents or in other geographic localities. Notably, however, orthohepadnaviruses have recently been identified in both Old and New World bats: specifically, long-fingered bat HBV (LBHBV) in Miniopterus fuliginosus from Myanmar (He et al, 2013), tent-making bat hepatitis B virus (TBHBV) in Uroderma bilobatum from Panama, roundleaf bat HBV (RBHBV) and horseshoe bat HBV (HBHBV) in Hipposideros cf.…”
Section: Introductionmentioning
confidence: 99%
“…This affects the ORF for HBcAg (cD153 and cR154), but not hepatitis B e antigen (HBeAg) (not shown), because this length polymorphism is located immediately carboxyterminal of the HBeAg processing site. None of the other human or ape HBV genotypes have this 2 amino acid insertion, but remarkably, there is a 5 amino acid insertion present at the same position in rodent hepadnaviruses (woodchuck hepatitis virus, 59 Arctic ground squirrel hepatitis virus, 60 and ground squirrel hepatitis virus 61 ; not shown). Because the efficiency of the backwards scanning mechanism depends on the distance between the 3Ј end of the core ORF and initiation of the polymerase ORF 43 (143 nucleotides for genotype B-G, 149 for genotype A, 158 for rodent hepatitis viruses), these length polymorphisms might help control the translation of the polymerase protein from the pregenomic mRNA in a genotype-dependent manner.…”
Section: A Standardized Nomenclature For Hbv Polymerasementioning
confidence: 99%
“…Chronic courses of hepadnavirus infections also occur in ducks, squirrels, and NHPs (Table 2). 30,96,112,113,[116][117][118]153 Whether chronic hepadnavirus infections occur in bats is unclear. 30 Among non-human hepaciviruses, studies reporting chronic infections are scarce.…”
Section: Chronic Courses Of Infection Occur In Diverse Hepatitis Virumentioning
confidence: 99%